Mechanical response of the sealing packer based on two rubber materials at high temperatures - Lan Jin; Zhangna Xue; Zidong Wang; Ruiyong Li; Jianlin Liu (Polymer Testing, 2023)
The compression packer is an important downhole oil production tool, and its failure is mainly attributed to the degradation of its embedded rubber cylinders under the action of high temperatures. In the present study we have made a comprehensive investigation on the mechanical response of the sealing packer based on two rubber materials at high temperatures. Firstly, by measuring the material parameters under different temperatures, we established the constitutive relationships of the two rubber materials (Aflas and Kalrez) in consideration of the temperature effect, in the light of the Mooney-Rivlin model. Next, the sealing performances of two optimized packers were analyzed including Aflas and Kalrez rubber cylinders. The effects of high temperature and the initial setting pressure on the sealing effects of these two optimized packers were probed based on the finite element analysis (FEA), and the ranges of temperature and initial setting pressure for best sealing were determined. This study can provide some ideas for the material selection and structural optimization for sealing packers, aiming to ensure the safe operation of the packers in severe environments.